Pulp sensibility to electric stimuli in the Caucasian population. (22nd May 2019) - Barczak, Katarzyna; Palczewska‐Komsa, Mirona; Wilk, Aleksandra; Nowicka, Alicja; Buczkowska‐Radlińska, Jadwiga; Wiszniewska, Barbara; Kotwas, Artur
Abstract: The aim of the study was to determine electric sensibility of the pulp in the Caucasian population depending on tooth morphotype, age and sex. Dental pulp sensibility was determined in 279 patients (2640 teeth). The study group consisted of 226 patients (1296 teeth), 110 men and 116 women aged 55–101. The control group consisted of 53 patients (1344 teeth), 23 men and 30 women aged 20–30. A statistically significant lower sensory threshold and increased pulp sensibility in the study group were noted. These affected the lower incisors, the second upper premolars and the first and second upper molar. The differences in the pulp sensibility were found in the region of maxillary central incisors, maxillary premolars, mandibular lateral incisors and mandibular premolars. The pulp sensibility threshold was lower for the aforementioned groups of teeth in the study group. The correlation between sensibility of the pulp and sex was not confirmed.